Revisiting the toolbox of discourse studies : new trajectories in methodology, open data, and visualization - Rheindorf, Markus, 1978- (Palgrave Macmillan, 2019)
This book revisits discourse analytic practice, analyzing the idea that the field has access to, provides, or even constitutes a 'toolbox' of methods. The precise characteristics of this toolbox have remained largely un-theorized, and the author discusses the different sets of tools and their combinations, particularly those that cut across traditional divides, such as those between disciplines or between quantitative and qualitative methods. The author emphasizes the potential value of integrating methods in terms of triangulation and its specific benefits, arguing that current trends in Open Science require Discourse Studies to re-examine its methodological scope and choices, and move beyond token acknowledgements of 'eclecticism'. In-depth case studies supplement the methodological discussion and demonstrate the challenges and benefits of triangulation. This book will be a valuable resource for students and scholars in Discourse Studies, particularly those with an interest in combining methods and working across disciplines. Markus Rheindorf is Senior Postdoctoral Researcher in the Department for Linguistics at the University of Vienna, Austria.- Resumé vydavatel
Keywords: diskurzivní analýza; diskuse; otevřená data; vizualizace informací; discourse analysis; discussion; open data; information visualization; elektronické knihy; monografie; electronic books; monographs